Keadilan Restoratif : Konsep dan Pengaturannya dalam Sistem Hukum Indonesia - Syah Awaluddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to explore the concept of Restorative Justice and its implementation in laws and regulations in Indonesia. Restorative justice is an approach to resolving criminal cases that prioritizes the restoration of relationships and social harmony rather than punishment. The research method used is a normative legal approach with analysis of primary and secondary legal materials. The results of the study show that the concept of restorative justice has been accommodated in various laws and regulations in Indonesia, such as the 1945 Constitution, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Regulation of the Indonesian Prosecutor's Office Number 15 of 2020, and Regulation of the Indonesian Police Number 8 of 2021. The implementation of restorative justice in Indonesia is manifested in the form of diversion, mediation, and termination of prosecution based on restorative justice. This study concludes that the implementation of restorative justice in Indonesia is an effort to create a more humane, inclusive, and sustainable criminal justice system.